Egy nap a Krsna tudatú hívők életéből
living in community, bakhta, shower several times a day, ritual painting the body, daily routine, mantra, meditation, prayers, marriage, how members became believers, vegetarianism, celibacy, income earning vs donations, simple life, helping people, charity, Béla Doszpod